The Influence of CEO Power on Compensation Contract Design - Abernethy, Margaret A.; Kuang, Yu Flora; Qin, Bo (The Accounting Review, 2015)
ABSTRACT We investigate whether CEO power influences a firm's decision to change its compensation system in response to regulatory and public pressure. In particular, we assess whether CEO power influences the choice of performance measures as a form of camouflage to minimize the impact of these reforms on their wealth. We examine one component of CEO pay, namely, the use of performance-vested stock option (PVSO) plans, and find that firms with powerful CEOs attach less challenging targets in the initial PVSOs granted to their CEOs. Such firms also appear to adopt PVSO plans early, and are more likely to do so when faced with public outrage over executive compensation. Our results suggest that powerful CEOs attempt to appease public outrage by quickly adopting PVSOs, but that adopting PVSOs early does not appear to be an optimal strategy for increasing shareholder value. Regulators intended that implementation of PVSOs would be beneficial to shareholders by improving the link between CEO pay and firm performance. However, our results indicate that powerful CEOs can negate some of the beneficial effect of PVSOs through their influence on adoption and choice of performance targets. Data Availability: All data used in this study are publicly available from the sources indicated in the paper.